Effects of sintering temperature on electrical properties of sheep enamel hydroxyapatite - (:unkn) unknown (IOP PUBLISHING LTD, 2017)
Bioceramics, especially calcium phosphate based bioceramics, whose examples are hydroxyapatite, and calcium phosphate powders have been widely used in the biomedical engineering applications. Hydroxyapatite (HA) is one of the most promising biomaterials, which are derived from natural sources, chemical method, animal like dental enamel and corals. The influence of sintering temperature on the electrical properties (i.e. DC conductivity, AC conductivity) of samples of sintered sheep enamel (SSSE) was studied in air and in vacuum ambient at room temperature. The sheep enamel were sintered at varying temperatures between 1000 degrees C and 1300 degrees C. DC conductivity results revealed that while dc conductivity of the SSSE decreases with increasing the sintering temperature in air ambient the values increased with increasing the sintering temperature in vacuum ambient. AC conductivity measurements were performed in the frequency range of 40 Hz - 10(5) Hz. The results showed that ac conductivity values decrease with increasing the sintering temperature.